2018
DOI: 10.1177/2055217317747626
|View full text |Cite
|
Sign up to set email alerts
|

Improved cognitive performance and event-related potential changes following working memory training in patients with multiple sclerosis

Abstract: BackgroundFew studies of cognitive rehabilitation in multiple sclerosis (MS) have targeted working memory specifically.ObjectiveWe examined the effects of n-back working memory training on cognitive performance and brain function in patients with MS.MethodsPatients with MS (n = 12) and healthy controls (HC; n = 12) underwent 20 sessions of n-back working memory training. Before and after training (pre- and posttest) cognitive event-related potential (ERP) measures were obtained during a 3-back task. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 51 publications
3
32
1
Order By: Relevance
“…Our findings, suggesting that early and late ERPs are differentially affected by Training-related modulation of the P2-N2-P3 complex: In our study, training-induced changes were observed already 200-300 ms after the stimulus onset. Such modulations of early responses, especially N2 and P3 responses, have been observed also in prior studies using differential experimental approaches either in training or in measuring its effects (Shiran and Brezniz 2011, Oelhafen et al 2013, Liu et al 2017, Covey et al 2018, Pergher et al 2018, Covey et al 2019. We did observe a significant session × group interaction already at P2 latency, although when the groups were examined separately a pre-post comparison showed an effect only in the control group.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our findings, suggesting that early and late ERPs are differentially affected by Training-related modulation of the P2-N2-P3 complex: In our study, training-induced changes were observed already 200-300 ms after the stimulus onset. Such modulations of early responses, especially N2 and P3 responses, have been observed also in prior studies using differential experimental approaches either in training or in measuring its effects (Shiran and Brezniz 2011, Oelhafen et al 2013, Liu et al 2017, Covey et al 2018, Pergher et al 2018, Covey et al 2019. We did observe a significant session × group interaction already at P2 latency, although when the groups were examined separately a pre-post comparison showed an effect only in the control group.…”
Section: Discussionsupporting
confidence: 86%
“…Especially its latter subcomponent, P3b, is associated to WM updating, allocation of attentional resources, and/or amount of resources demanded in the current task (Donchin et al 1986, Dien et al 2004, Lenartowicz et al 2010, Daffner et al 2011. There is some evidence, mostly from studies utilizing differential experimental approaches such as the Sternberg task (Shiran and Brezniz 2011), a go/nogo task (Liu et al 2017), but also a very recent study utilizing the n-back task (Covey et al 2018), suggesting that ERPs especially at N2-P3 latencies are modulated by WM training. Although those fMRI studies have mostly encountered activation decreases at the early processing stages (Salmi et al 2018), there are several ERP studies that have reported increased responses in the direct comparisons between the pretest and posttest responses (e.g., Berry et al 2010, Shiran and Brezniz 2011, Covey et al 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RehaCom cognitive training software has similarly demonstrated efficacy in its ability to treat PS specifically in several samples of persons with MS [e.g., (4144)]. Similarly, Covey et al (45) showed a n-back training program to results in improved functioning on working memory, PS, complex attention and reasoning. Pedulla et al (46) utilized an at-home training program, the COGNI-TRAcK in 28 persons with MS, noting significant improvement on verbal learning and recall, verbal fluency, sustained attention, concentration and PS.…”
Section: Discussionmentioning
confidence: 99%
“…Given the reliability of our classification approach, we believe that univariate measures summarising the strengths of expression of the connectivity patterns for stimulus domains and processes should be explored in studies of group and individual differences in WM and as outcome measures in trials that seek to enhance WM functions. The latter application is particularly promising given recent studies showing that the functional connectivity of the WM network is amenable to modulation by non-invasive brain stimulation 55 and augmentation by focused cognitive training 56,57 . Future work should also focus on analysing directed information flow using effective connectivity methods to determine how transitions between these task-evoked processing states are orchestrated within the human brain 29,58,59 .…”
Section: Discussionmentioning
confidence: 99%